Knowledge Development Through Information Technology in Salaf Pesantren - Hasyim, Muhammad (Academia Publication, 2023)
As major institutions, Pesantren Sidogiri and Pesantren Langitan have long been developing information technology (IT) within their pesantren environments. At Pondok Pesantren Sidogiri in Pasuruan, the Agency for System and Information Technology Development (BPSTI) was established in 2013 to manage all information system needs (software) and oversee website services (Sidogiri.net) as well as pesantren administration. Meanwhile, at Pondok Pesantren Langitan in Tuban, a similar initiative led to the launch of the Majalahlangitan.com website in 2013. Over time, Langitan formed the Media Dakwah Langitan, an umbrella organization managing Majalah Langitan (print), Langitan TV (YouTube channel), radio streaming, and various social media platforms. This study examined the role of IT in the development of Islamic scholarship at these two pesantren through a qualitative study approach, presenting findings in a narrative-descriptive format. Using a multisite study method, it focuses on two renowned pesantren in Java. The results highlight that IT plays a crucial role in advancing the academic aspects of both pesantren. Generally, its implementation falls into three main categories: pesantren governance, dissemination of Islamic knowledge, and support for educational references.